In Vivo Functional Ultrasound (fUS) Real‐Time Imaging and Dosimetry of Mice Brain Under Radiofrequency Exposure. Issue 4 (29th April 2022) - Orlacchio, Rosa; Percherancier, Yann; Poulletier De Gannes, Florence; Hurtier, Annabelle; Lagroye, Isabelle; Leveque, Philippe; Arnaud‐Cormos, Delia
Abstract : This study aims to analyze in real‐time the potential modifications induced by low‐level continuous‐wave and Global System for Mobile Communications radiofrequency (RF) exposure at 1.8 GHz on brain activation in anesthetized mice. A specific in vivo experimental setup consisting of a dipole antenna for the local exposure of the brain was fully characterized. A unique neuroimaging technique based on a functional ultrasound (fUS) probe was used to observe the areas of mice brain activation simultaneously to the RF exposure with unprecedented spatial and temporal resolution (~100 μm, 1 ms) following manual whisker stimulation using a brush. Numerical and experimental dosimetry was carried out to characterize the exposure and to guarantee the validity of the biological results. Our results show that the fUS probe can be efficiently used during in vivo exposure without interference with the dipole. In addition, we conclude that exposure to brain‐averaged specific absorption rate levels of 2 and 6 W/kg does not introduce significant changes in the time course of the evoked fUS response in the left barrel field cortex. The proposed technique represents a valuable instrument for providing new insights into the possible effects induced on brain activation under RF exposure. For the first time, brain activity under mobile phone exposure was evaluated in vivo with fUS imaging, paving the way for more realistic exposure configurations, i.e. awake mice and new signals such as the 5 G networks. © 2022 Bioelectromagnetics Society.